The testing of the MEDROPLAN drought management guidelines [Part 1. Components of drought planning. 1.3. Methodological component] - The MEDROPLAN team (Drought management guidelines technical annex, 2007)
According to the MEDROPLAN project contract, Work-package 8 was devoted to testing the drought management guidelines drafted in Work-package 6. Testing had be carried out by each partner with reference to a different region or watershed than the one where the risk analysis has been carried out. The outcome of such a process were conclusion reports by each partner on the testing of the Guidelines, with conclusions and recommendations on the applicability of the Guidelines to each country, and with possible improvements to the Guidelines.